Morphological response and growth of cork oak (Quercus suber L.) seedlings at different shade levels - Cardillo, E; Bernal, C J (Forest Ecology and Management, 2006)
In spite of the importance of shade tolerance in silviculture, some species such as cork oak (Quercus suber L.) have not been well characterized. This work aims to describe the response of cork oak seedlings to a light gradient in their ﬁrst growing period. The seedlings were grown under different mesh ﬁlters and were watered to full ﬁeld capacity of the soil. The response to different light levels was studied in terms of morphology and growth, measuring heights, diameters, photosynthetic apparatus dimensions and shoot and root biomass. There were three plant extractions in April, June and October. The greatest morphological plasticity was noticed in the size of the leaves, which changed from 1.8 cm 2 under full sunlight to 5.8 cm 2 in maximum shade. The cork oak seedlings endured light levels of 20% at relative growth rates (RGR) similar to those under full sunlight. However, light intensities under 50% produced a smaller accumulation of root biomass. Plants under 5% of light showed clear symptoms of etiolation and their net assimilation rate was practically zero. These results will prove useful in silviculture, for instance, when determining the grade of protection in cork oak reforestations, as well as when deciding the system and period of regeneration and when regulating the liberation cuts of parent trees in stands of cork oak.
Keywords: Cork oak; growth analysis; Quercus suber; shading; tolerance

Morphological response and growth of cork oak (Quercus suber L.) seedlings at different shade levels - Cardillo, E.; Bernal, C. J. (Forest Ecology and Management, 2006)
In spite of the importance of shade tolerance in silviculture, some species such as cork oak (Quercus suber L.) have not been well characterized. This work aims to describe the response of cork oak seedlings to a light gradient in their ﬁrst growing period. The seedlings were grown under different mesh ﬁlters and were watered to full ﬁeld capacity of the soil. The response to different light levels was studied in terms of morphology and growth, measuring heights, diameters, photosynthetic apparatus dimensions and shoot and root biomass. There were three plant extractions in April, June and October. The greatest morphological plasticity was noticed in the size of the leaves, which changed from 1.8 cm 2 under full sunlight to 5.8 cm 2 in maximum shade. The cork oak seedlings endured light levels of 20% at relative growth rates (RGR) similar to those under full sunlight. However, light intensities under 50% produced a smaller accumulation of root biomass. Plants under 5% of light showed clear symptoms of etiolation and their net assimilation rate was practically zero. These results will prove useful in silviculture, for instance, when determining the grade of protection in cork oak reforestations, as well as when deciding the system and period of regeneration and when regulating the liberation cuts of parent trees in stands of cork oak.
Keywords: Cork oak; growth analysis; Quercus suber; shading; tolerance

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - VILLAR-SALVADOR, P; Planelles, R; Enrı́quez, E; Rubira, J.Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading

Nursery cultivation regimes, plant functional attributes, and field performance relationships in the Mediterranean oak Quercus ilex L. - Villar-Salvador, P.; Planelles, R.; Enrı́quez, E.; Rubira, J. Peñuelas (Forest Ecology and Management, 2004)
In this study we have addressed the effect of nitrogen fertilisation and shading used during nursery growth on the functional quality of Quercus ilex L. (holm oak) seedlings and their outplanting performance in an abandoned continental Mediterranean cropland. Three N fertilisation regimes: high and low fertilisation (154 and 34 mg N per plant, respectively) and no fertilisation, combined with two shade levels (full sun and 45% shade) were studied. Fertilisation increased the shoot size, shoot to root mass ratio (S/R), root N, and both shoot and root P concentration of the plants produced in the nursery. Fertilisation also enhanced the capacity of new root formation. Neither tissue K nor root mass was affected by N fertilisation. Shading increased S/R and root K concentration but reduced both shoot and root N concentration. Two years after planting, unfertilised seedlings had higher mortality and grew signiﬁcantly less than those cultivated at both a low and a high fertilisation level. Shading during nursery growth had no inﬂuence on the outplanting performance of holm oak seedlings. Plants with a larger shoot and higher S/R had lower mortality and grew faster than those with a smaller shoot and lower S/R. Outplanting performance of holm oak seedlings was related with root N and P concentration and with RGC. No relationship was found with either shoot nutrient concentration or root mass. We conclude that high N fertilisation of holm oak seedlings in the nursery can improve their early ﬁeld establishment in the afforestation Mediterranean abandoned croplands.
Keywords: Afforestation; Holm oak; nitrogen; nursery fertilisation; root growth capacity; shading